Critical Study of Female Prayer Imams in the Perspective of Islamic Education - Qomariyah, Siti; Cahyadi, Wendy Asswan (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
Amina Wadud, a Muslim feminist who organizes congregational prayers, the imam is a woman, the congregation is male and female. This research is library research, with a descriptive qualitative analysis method. This research examines the texts of the Qur'an - Hadith, methods of interpreting the Qur'an, how to understand Hadith and the method of ijtihad which is used as a legal basis for opinions which say that women can lead congregations that are mostly men, then analyze and criticize them by perspective of Islamic education. Results of this research: Hermeneutics is not a method of interpreting the Qur'an and is not based on Islamic creeds. Ijtihad must also be based on Islamic beliefs, not based on gender equality and can only be carried out by mujtahids who meet the requirements. The area of ijtihad is the zonni/mutasyabihat texts, namely texts whose meaning is still unclear. To obtain the strongest proposition, if there are two propositions, it is better to use two propositions rather than ignoring one of them (I'mal Ad-Dalilayn Awla Min Ihmal Ahadihima). Based on this, the opinion that allows women to be prayer leaders for men is a weak opinion. It is permissible for female educators to become imams for boys who are not yet mumayyiz. However, if the congregation is all boys who are not yet mumayyiz, then it is not considered to be praying in congregation. The incident of Umm Waraqah leading a boy who had not yet mumayyiz was the most effective application of educational methods in teaching prayer, namely practice, example and habituation.